A comparative study on pyrolysis reactivity and gas release characteristics of biomass and coal using TG-MS analysis. Issue 17 (2nd September 2018) - Wei, Juntao; Liu, Xia; Guo, Qinghua; Chen, Xueli; Yu, Guangsuo
ABSTRACT: Pyrolysis reactivity and gas release characteristics of biomass and coals were comparatively investigated using TG-MS. In addition, chemical compositions and structures of tested samples were determined to correlate pyrolysis gas release characteristic. It was found that pyrolysis reactivity and gaseous product release were hardly varied with pyrolysis heating rate. Furthermore, pyrolysis rates of two biomass samples were greater than those of coals, which were mainly attributed to the chemical compositions and the gaseous product evolution process. The result also showed that gaseous product release during pyrolysis process was related to the presence of different functional groups in samples.